The Implementation of Think Talk Write Learning Strategy to Improve Student’s Learn Activities in Biology Learning Class X-1 SMA Al Islam 1 Surakarta of 2009/2010 Academic Year - Dwitya Nadia Fatmawati; Slamet Santosa; Joko Ariyanto (Universitas Sebelas Maret, 2013)
The purpose of the research to improve student learning activities in teaching and learnig activities with the implementation of Biology learning strategy Think Talk Write on Environmental Pollution material. This research is a classroom action research. The experiment was conducted in two cycles, with each cycle consisting of the planning, observation, evaluation, analysis, and reflection. Subjects were students of class XI SMA Al Islam 1 Surakarta academic year 2009/2010. Source of data derived from teacher and student information, observation, and documentation. Techniques and tools of data collection is a questionnaire, observation, and interviews. Validate data using triangulation techniques of data sources. Data analysis techniques used are qualitative analysis. Research procedure is a spiral model of inter-related. The results showed that the application of learning strategies can improve student activities in biology learning in class X-1 SMA Al Islam 1 Surakarta 2009/2010 academic year. Improved student learning activities can be viewed through a questionnaire and observation sheet. The average percentage based on observation of student activity sheets for 41.90% of pre cycle, a cycle of 73.07% and 87.23% for cycle 2.Questionnaire pre-cycle calculation results indicate student activity at 70.49%, a cycle of 73.83%, and the second cycle result indicate that student activity of 77.96%. Key Words: Think talk write learning strategy, student activity, biology learning.